Internationalization policies of higher education in Argentina: the promotion of the university abroad - Garcia, Pablo Daniel; Claverie, Julieta; Fernández Lamarra, Norberto Rafael (Universidade Estadual de Campinas, 2019)
The internationalization of higher education is a phenomenon close in time, which has gained more momentum towards the end of the 1980s and the beginning of the 90s as a result of changes in economies and societies due to the globalization process. In Argentina and the region, the internationalization of higher education has been accentuated in the last two decades. This tendency is observed in the important growth of the activities that academics from Latin American universities develop in foreign universities, the high number of students who study at universities in other countries; the multiplication of distance education programs; the appearance of undergraduate and postgraduate degrees with double degrees; the emergence and consolidation of national and international university networks and for regional convergence, among other aspects. This article aims to account for general aspects, guidelines, objectives and strategies implemented by the internationalization policies of the Argentine Republic in recent decades and in particular seeks to account for an innovative way of developing internationalization: the promotion of the universities abroad. The article has been built from the compilation and public information on the development of programs linked to the internationalization of Higher Education by the Ministry of Education of Argentina. The article includes a theoretical synthesis of the contemporary debates on the internationalization of higher education to then give an account of the main actions of public policy in regard to the scope and challenges still pending in the internationalization of higher education in the country and in particular, the Promotion Program of the Argentinian University.